A history of the strategic implications of the Great Recession and its aftermath on U.S. national defense - Young, Stephanie; Gentile, Gian P.; Sacks, Benjamin J.; Edenfield, Nathaniel; Givens, Adam (RAND Corporation, 2023)
The Great Recession began in 2007, when a contraction in the U.S. housing market led to widespread losses in the financial sector and, subsequently, to economic shocks around the world. By December 2007, the country was officially in recession, and it would not emerge from this contraction for 18 months. Although national security decisionmaking was not immediately affected by the recession, uncertainties created by short-term political measures to address the deficit meant that DoD had to fundamentally reconsider its ways and means of ensuring national security in the 2010s. This history considers the Great Recession's reverberations on the DoD as senior leaders in the Office of the Secretary of Defense (OSD) and the Joint Staff worked to shift from a decade of counterterrorism operations toward future threats amid a dynamic threat environment and budgetary uncertainty
"National Security Research Division" -- title page
Keywords: USA -- Department of Defense; Geschichte 2007-2016; Haushaltsplan; Rezession; Sicherheitspolitik; United States / Department of Defense / Appropriations and expenditures; Budget / United States / History / 21st century; Recessions / United States / History / 21st century; National security / United States; Terrorism / United States / Prevention; United States / Economic policy / 2009-; Récessions / États-Unis / Histoire / 21e siècle; United States / Department of Defense; Budget; Economic policy; Expenditures, Public; National security; Recessions; Terrorism / Prevention; United States; Since 2000; History